Evaluation of Lotus corniculatus for increasing the efficiency of growth in young deer : a thesis presented in partial fulfilment of the requirement for the degree of Masters of Applied Science, Animal Science option at Massey University - Adu, Emmanuel Kwadwo (Massey University, 1997)
A grazing trial with lactating red deer (Cervus elaphus) hinds and their calves (EXPERIMENT 1), and an indoor digestion and calorimetric study (EXPERIMENT 2) were conducted at Massey University, New Zealand during 1996, to measure the feeding value of Lotus corniculatus compared to perennial ryegrass (Lolium perenne)/white clover (Trifolium repens) pasture for increasing the efficiency of growth in young deer. Half of the hinds and their calves were grazed on Lotus corniculatus and the other half were grazed on perennial ryegrass/white clover pasture during summer (Chapter Three) in a rotational grazing system. Half of the hinds in each group suckled pure red calves with the other half suckling hybrid (0.25 elk : 0.75 red deer) calves. The indoor experiments (Chapter Four) involved feeding one animal of a pair on either freshly cut perennial ryegrass or freshly cut Lotus corniculatus during autumn and spring, in metabolism cages and calorimetry chambers at maintenance (1M) and twice maintenance (2M) levels of energy intake. 1. EXPERIMENT 1 (CHAPTER THREE). Liveweight gains of hinds and their calves, weaning weight of calves and voluntary feed intake of hinds were measured on Lotus corniculatus or perennial ryegrass/white clover pasture during lactation in summer 1996. The percentage of dead matter in both the forage on offer and diet selected was lower in Lotus corniculatus than in perennial ryegrass/white clover pasture. The condensed tannin (CT) levels in Lotus corniculatus and perennial ryegrass/white clover pasture were 21 g and 1.6 g total CT/kg DM respectively. Organic matter digestibility (OMD) was higher for Lotus corniculatus than for perennial ryegrass/white clover pasture. Hinds grazing Lotus corniculatus had higher voluntary feed intake (VFI) and liveweight change than hinds grazing perennial ryegrass/white clover pasture, and liveweight gain and weaning weight of calves were greater on lotus. Liveweight gain and weaning weight of hybrid deer were superior to pure red deer calves, with pre-weaning liveweight gain of hybrid deer calves grazed on Lotus corniculatus exceeding 500 g/d for the first time. CT in Lotus corniculatus was more tightly bound in red deer oesophageal fistula (OF) extrusa samples than in comparable studies with sheep. 2. EXPERIMENT 2 (CHAPTER FOUR) Energy losses as methane, urine and heat were consistently lower when the deer were fed Lotus corniculatus (21 g total CT/kg DM) than perennial ryegrass (< 1 g total CT/kg DM), but faeces energy losses were similar for the two forages. The efficiency of utilisation of ME for growth (kg) was lower in autumn-grown than in spring-grown perennial ryegrass, and tended to be greater in autumn-grown Lotus corniculatus than autumn-grown perennial ryegrass. No significant differences existed in faecal N and urine N losses in deer fed the two forages, and N retention was similar in deer fed Lotus corniculatus and perennial ryegrass. Presence of CT-binding salivary proteins in deer but not in sheep is advanced as a reason for N retention not being greater on lotus. 3. The overall conclusion from this thesis was that as a summer feed during deer lactation, the feeding value of Lotus corniculatus is higher than that of perennial ryegrass/white clover pasture but essentially similar to that of other special purpose feeds developed for deer production such as chicory (Cichorium intybus) and red clover (Trifolium repens). The most cogent explanations for the higher performance in deer fed Lotus corniculatus is the higher VFI and the greater efficiency with which ingested energy was utilised. Because of the presence of salivary CT-binding proteins in deer, forages with higher CT concentrations are suggested for the realisation of the beneficial effects of forage CT on the efficiency of protein digestion in farmed deer. Two such forages are sulla (Hedysarum coronarium; 35-60 g CT/kg DM) and Lotus pedunculatus (50-100 g CT/kg DM). The incorporation of Lotus corniculatus into the pastoral agricultural system of NZ may be hindered by the slow establishment of the plant, and by the special management system required. It may be better suited agronomically to warm low to medium fertility hill country conditions, such as found in East Coast areas, where competition from other plant species is less.
Keywords: Deer; Lotus corniculatus; Feeding and feeds; New Zealand